The Relationship Between Intellectual Competence, Non-Material Incentives, Work Environment And Employee Performance - Harjo Lukito (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2022)
The goal of this study is to examine how improving intellectual competence, non-material incentives, work environment might improve employee performance. In order to gather information and examine the correlation between the variables under investigation, this study employs a quantitative approach and a sample of 67 employees at PT. Bunga Jaya Jati Bintang Mojokerto as responders. Several linear regression techniques were used to examine the data after it was collected using a questionnaire. According to the study's findings, employee performance is influenced by intellectual ability. The work environment has also been demonstrated to have a substantial impact on employee performance, and non-material incentives have been shown to have an impact on employee performance.